Quando la giustizia incontra il minore L'esperienza dell'aula di audizione protetta in Italia (Pesaro, 11 maggio 2013) - Pozzolini, Flavia (Atti, 2013)
This volume collects the reports from the conference Quando la giustizia incontra il minore, held in Pesaro on 11th May 2013. The conference, to which jurists and professionals of the sector took part, was an important opportunity for discussion on the ways to correctly protect the hearing of minors within the many processes involving them, and on the consequent need, in the courts, for premises which are adequately equipped for that purpose. The creation of protected listening rooms in Italian courts was the main national project of the Soroptimist International of Italy during the two-year period going from 2011 to 2013; to date, 40 rooms have been completed and a further 10 are under construction. This project is also expected to continue in the upcoming two years. Soroptimist International is a women's association made up of women with high qualifications in the workplace. The association operates for the promotion of human rights, the improvement of women's condition and the acceptance of diversity through a wide array of projects. Their name comes from the Latin words soror and optima. The first Soroptimist club was born in the United States in 1921, whereas the first Italian club was founded in Milan in 1928. There are currently 143 Italian clubs with about 6.000 members. The Soroptimist International of Italy publishes the magazine "La voce delle donne - Soroptimist news" and has an institutional website: www.soroptimist.it. Foreword by the Italian Minister Annamaria Cancellieri